Low detection rate in visual observations of stream salmonids in winter - Jaakko Erkinaro; Aki Mäki-Petäys; Ari Huusko; Jorma Kuusela; Eero Niemelä (Journal of Freshwater Ecology, 2018)
Visual methods in detecting juvenile Atlantic salmon (Salmo salar L.) in winter were assessed, both in a natural subarctic river in northernmost Finland (70°N) and in an experimental flume, both under ice and in open water. Video surveillance was used under different conditions, and at one field site, data from video cameras and snorkeling were compared with subsequent electrofishing at the same site. In addition, the activity and visibility of juvenile salmon in cold water was studied under controlled experimental conditions using video, PIT tags and a known number of fish present in a laboratory flume. We documented a poor underwater detection rate for juvenile Atlantic salmon by visual observations in wintertime, both in day and night, and both with and without ice cover. Comparison of successively conducted field experiments at the same site resulted in two salmon parr observations by snorkeling, one by video and 63 individuals by electrofishing. In the laboratory experiment the maximum proportion of fish observed was 33 and 50% of those present in the flume by using video-surveillance and PIT tracking, respectively. Both methods indicated that salmon parr were significantly more visible during the darkness compared to the illuminated hours. These results pose critical questions to the traditional visual observation methods used in winter studies on stream salmonids.